Is Anterior Release Obsolete or Does It Play a Role in Contemporary Adolescent Idiopathic Scoliosis Surgery? A Matched Pair Analysis. Issue 3 (March 2020) - Lonner, Baron S.; Haber, Lawrence; Toombs, Courtney; Parent, Stefan; Shah, Suken A.; Lenke, Lawrence; Sucato, Daniel; Clements, David; Newton, Peter O.
Abstract : Study Design: A retrospective analysis of a prospectively collected database was performed. Objective: The purpose of this study is to compare 3-dimensional correction associated with the anterior release (AR) and contemporary posterior instrumentation versus posterior-only surgery. Summary of Background Data: The role of AR as a tool in the treatment of adolescent idiopathic scoliosis (AIS) has seen a decline with the popularization of thoracic pedicle screw instrumentation. Methods: Five surgeons were queried for all surgical thoracic AIS cases from 2003 to 2010 treated with thoracoscopic AR/fusion and contemporary posterior instrumentation and fusion and thoracic pedicle screw instrumentation (>80% screws) with 2-year follow-up. These cases were then matched with posterior spinal fusion only cases from a multicenter prospective database. The 2 groups were matched on the basis of major curve magnitude within 5 degrees, T5-T12 kyphosis within 9 degrees, and angle of trunk rotation within 9 degrees. Radiographic and clinical parameters were compared for the 2 groups. Continuous variables were analyzed with analysis of variance and categorical dependent variables with the χ 2 test. Results: A total of 47 cases of AR were matched to 47 (1:1 match) posterior spinal fusion cases. Preoperative parameters were similar between groups ( P >0.05). Postoperatively, AR cases had a lower major curve (20 vs. 25 degrees, P =0.034; 72% vs. 66% correction, P =0.037). T5-T12 kyphosis was greater in the AR cases (26 vs. 20 degrees; P =0.005). The angle of trunk rotation was similar for the groups. Anchor density was lower in the AR group (1.6 vs. 1.9; P <0.0001). There were 3 complications associated with the AR: 1 pneumothorax and 2 conversions to minithoracotomies for failure to maintain single lung ventilation. Conclusions: AR improves coronal and sagittal plane correction in contemporary AIS surgery with a satisfactory complication profile with less pedicle screw density required for clinically similar corrections. A further prospective study on the benefits of AR may help define specific indications.